A Study of Islamic and Arab Markets' Role in Revitalizing Urban Spaces - Lotfy, Mohamed Yasser; Soliman, Abdullah; Mandour, Alaa (Journal of Islamic Architecture, 2015)
Market places have occupied a major role in most cities around the world, being a site for more than just economic interactions, but rather a cultivating agent for social and cultural growth. The Arab and Islamic cities have a proud history of market places, most of the times being the main core of the city, with urban development encompassing it, and till the present day market places are in the heart of most communities. The modern city brought with it a devaluing of the traditional market places, making it a tourist attraction as in the case of "khan el Khalil",or leaving it to rust like "bab el louq" market. Those markets while playing a big role historically, modern city planning moved the services and markets into other form, thus becoming less important, abandoned, or even demolished at cases.The issue at hand deals with how the contemporary urban planning affected market places, with emphasis on closed markets (Bab el-louk)which can be said to be the successor of the ancient Bazaar or Wekala.Â  Bal el-Louk market was once in the heart of Cairo and vital part of its community life, but now the market after more than a 100 years, is in ruins, but hope is not yet all lost, since the market can still be revived and revitalized.To tackle this issue a combination of comparative and field studies must occur. On the one hand, comparative studies with markets in the US or closed markets in European cities such as Paris or Copenhagen would be done to find the necessary elements and goals that would make those markets vital, and the necessary steps to revitalize our own forgotten markets. The other study would have to deal with the current condition of bab el louk market in Cairo, finding out the reason behind its demise, the owners and users feedback on said market, and the opportunities for change.With the results of the studies, general recommendations would be made for the revitalization of the Egyptian marketplaces, using an urban framework that would lead to those markets be available for costumers again and back to playing their major cultural and social rule.